Nexus between Air Pollution and Neonatal Deaths: A Case of Asian Countries - Anwar, Asim (Int J Environ Res Public Health, 2019)
The rapid economic growth in Asian countries has witnessed a persistent increase in air pollution complementing adverse health challenges for children in these countries. Quantification of health effects attributable to air pollution (PM(2.5)) is important in policy implications to tackle air pollution and associated health problems. This study aims to explore the nexus between air pollution and neonates’ deaths embedded in acute respiratory infection. We collected panel data from the 12 most vulnerable Asian countries over the period of 2000–2017 and analyzed through the fixed-effect model. Empirical results show a positive relation between air pollution, temperature, and neonates’ deaths in the studied Asian countries. The results have attested negative impacts of income and education while positive effect of population density on neonates’ deaths due to acute respiratory infection. Diagnostic and prognostic measures have checked the pace of the respiratory diseases caused by PM(2.5) and resultant deaths in Asian countries; yet alarming factors, like mounting industrial air pollution and rapid expansion of industrial zones in urban areas, need to be addressed in policy implications for long term sustainable solutions.